H∞ control for uncertain discrete-time MJSs with piecewise-constant transition probabilities subject to multiple intermittent sensor faults. Issue 15 (October 2020) - He, Zhang; Lu, Junwei; Chu, Yuming; Li, Yongmin; Xu, Shengyuan; Zhang, Zhengqiang
Abstract: This paper addresses the problem of H ∞ control for an uncertain discrete-time Markov jump system subject to multiple intermittent sensor faults. The intermittent fault considered in this paper is formulated as a probabilistic event and is additive to the normal signal of a sensor in systems. The occurrence of the intermittent fault is assumed to satisfy the Bernoulli random binary distribution which takes values of either 0 or 1. The nonlinearity is related to time-varying delay and satisfies a sector-bounded condition. The Markov chain is considered as finite piecewise-constant. To keep the desired performance of the faulted system, a dynamic full-order output-feedback controller is presented. By using the Lyapunov method and inequality techniques, exponential mean-square stability criteria of the fault-free closed-loop system are obtained and a design of the dynamic full-order output-feedback controller is given. Finally, a numerical example is given to show effectiveness and advantage of the obtained results.